Near-Forward Rescattering Photoelectron Holography in Strong-Field Ionization: Extraction of the Phase of the Scattering Amplitude - Zhou, Yueming; Tolstikhin, Oleg I; Morishita, Toru (Physical review letters, 2016)
We revisit the concept of near-forward rescattering strong-field photoelectron holography introduced by Y. Huismans et al. [Science 331, 61 (2011)]. The recently developed adiabatic theory is used to show how the phase of the scattering amplitude for near-forward rescattering of an ionized electron by the parent ion is encoded in and can be read out from the corresponding interference pattern in photoelectron momentum distributions (PEMDs) produced in the ionization of atoms and molecules by intense laser pulses. A procedure to extract the phase is proposed. Its application to PEMDs obtained by solving the time-dependent Schrödinger equation for a model atom yields results in good agreement with scattering calculations. This establishes a novel general approach to extracting structural information from strong-field observables capable of providing time-resolved imaging of ultrafast processes.